Academic Supervision in Educational Institutions - Akrom Maulidi; Agus Holid; Supardi; Agus Gunawan (Jurnal Multidisiplin Madani, 2024)
This article discusses academic supervision in educational institutions as an important component in the management and improvement of the quality of education. Academic supervision is a series of activities that aim to help teachers develop their ability to manage the learning process. This study describes the stages in academic supervision which include planning, implementation, results analysis, follow-up plans, and reporting. In planning, supervisors need to draw up schedules, determine problem focuses, and develop supervisory instruments. The implementation of supervision is carried out through various methods such as classroom observation, interviews, and discussions with teachers. The results of the supervision analysis are used as a basis to formulate follow-up and improvement recommendations. This study concludes that planned and systematic academic supervision plays a crucial role in improving teacher competence and the quality of learning in educational institutions